An ecological study of geographic variation and factors associated with cesarean section rates in South Korea - Kim, Agnus M. (BMC Pregnancy Childbirth, 2019)
BACKGROUND: Korea is in a condition where the impact of patient and supplier factors on cesarean section rates can be clearly described. The cesarean section rates in Korea are among the highest in the world while the number of obstetricians is decreasing sharply. This study aimed to investigate the geographic variation in cesarean section rates in Korea and its factors. METHODS: The data were obtained from the National Health Insurance database in Korea in 2013. We calculated the age-standardized and crude cesarean section rates of 251 districts in Korea and variation statistics. A linear regression analysis was performed to determine factors for cesarean section rates. RESULTS: The overall cesarean section rate in Korea was 364.6 cases per 1000 live births. The deprivation index score was strongly associated with the increase in the cesarean section rate while the density of hospital obstetricians and hospital beds showed a negative association. Average maternal age and total fertility rate showed a negative relationship with the cesarean section rate. CONCLUSIONS: Korea is suffering from a continuing decrease in obstetricians. Our study shows that this decline has more of an effect on mothers in the disadvantaged areas. Securing equal access to obstetric care among areas is necessary, and measures to encourage obstetricians and mothers not to opt for cesarean section are required. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12884-019-2300-0) contains supplementary material, which is available to authorized users.